2015
DOI: 10.5551/jat.28134
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D and the Incidence of Peripheral Artery Disease in the Elderly: The Pro.V.A Study

Abstract: Aim: This study was conducted to examine whether low serum levels of 25-hydroxyvitamin D (25OHD) are associated with a higher risk of incident peripheral artery disease (PAD) in a representative group of elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Three studies 13 15 18 have examined the relationship between vitamin D and PAD in the general population. Of those, two 13 15 were conducted using the US National Health and Nutrition Examination Survey (NHANES) 2001-2004 data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies 13 15 18 have examined the relationship between vitamin D and PAD in the general population. Of those, two 13 15 were conducted using the US National Health and Nutrition Examination Survey (NHANES) 2001-2004 data.…”
Section: Discussionmentioning
confidence: 99%
“…Some prior studies have reported that low serum 25(OH)D concentrations are associated with a higher prevalence of PAD, 12 13 14 15 16 whereas others have not. 3 17 18 …”
Section: Introductionmentioning
confidence: 99%
“…follow-up of 4.4 years[16]. In the latter study participants with 25(OH)D concentrations <25 nmol/L had no increased risk of developing PAD as defined by an ABPI of <0.9.…”
mentioning
confidence: 83%
“…Five of these studies were excluded because PAD cases and/or non-PAD controls were not defined or 25(OH)D concentrations were not reported. One study was excluded as it was not a casecontrol investigation [16]. One study included patients with abdominal aortic aneurysm (AAA) as controls and since these individuals cannot be assumed to be healthy or not have concomitant PAD [28], this study was excluded [12].…”
Section: Selection Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation